2010
DOI: 10.1099/ijs.0.015917-0
|View full text |Cite
|
Sign up to set email alerts
|

Deinococcus wulumuqiensis sp. nov., and Deinococcus xibeiensis sp. nov., isolated from radiation-polluted soil

Abstract: The taxonomic positions of two gamma- and UV-ray-resistant strains isolated from radiation-polluted soil in north-west China were determined in a polyphasic study. The organisms, designated R12T and R13T, were Gram-stain-positive, non-spore-forming cocci, which contained MK-8 as the major respiratory quinone and C16 : 1 ω7c and C16 : 0 as major fatty acids. The cell walls of strains R12T and R13T contained ornithine. Phylogenetic analysis based on 16S rRNA gene sequences and DNA–DNA hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Similar to the prototype strain of the Deinococcus genus, D. radiodurans R1, D. wulumuqiensis R12 is also well known for its excellent ability to resist extremely high doses of gamma and UV radiation [45]. In order to explore its potential applications in biocatalysis, growing and resting cells of this strain were applied as biocatalysts in the conversion of HMF to form HMFCA.…”
Section: Growing and Resting Deinococcus Cells As Catalysts In Hmf Oxmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the prototype strain of the Deinococcus genus, D. radiodurans R1, D. wulumuqiensis R12 is also well known for its excellent ability to resist extremely high doses of gamma and UV radiation [45]. In order to explore its potential applications in biocatalysis, growing and resting cells of this strain were applied as biocatalysts in the conversion of HMF to form HMFCA.…”
Section: Growing and Resting Deinococcus Cells As Catalysts In Hmf Oxmentioning
confidence: 99%
“…Nevertheless, employing whole-cells or isolated enzymes derived from extremophiles for biocatalysis in a general manner is just beginning to be implemented experimentally. Recently, a Deinococcus sp, designated as Deinococcus wulumuqiensis R12, was isolated from radiation-polluted soil [45,46]. Previous studies showed that it is phylogenetically more closely related to a prototype strain of the Deinococcus genus, namely Deinococcus radiodurans R1 [47].…”
Section: Introductionmentioning
confidence: 99%
“…It was isolated from the radiation-contaminated soils in the Xinjiang Uigur Autonomous Region of northwest China. Strain R12 is a Gram-positive, reddish orange, non-spore-forming coccus, with gamma radiation resistance to >10 kGy and UV resistance to >700 J m -2 (7). This strain shows a higher tolerance for gamma radiation and UV light than does D. radiodurans R1.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Strain R13 is an aerobic, Gram-positive, red-pigmented coccus with gamma-radiation resistance to >10 kGy and UV resistance to >700 J · m -2 (7). R13 produces deinoxanthin, and its color is deeper than that of D. radiodurans .…”
Section: Genome Announcementmentioning
confidence: 99%